Antenatal depression among pregnant women in Ethiopia: An umbrella review - Mesfin Abebe; Yordanos Sisay Asgedom; Amanuel Yosef Gebrekidan; Tsion Mulat Tebeje (PLoS ONE, 2025)
Introduction Antenatal depression, ranging from mild to severe, is influenced by hormonal changes during pregnancy and childbearing years, making it a significant public health issue. Antenatal depression, with its far-reaching effects on mothers, infants, and children, continues to be a significant public health issue in developing countries such as Ethiopia. Research on antenatal depression in Ethiopia has produced varied results. Although previous systematic reviews and meta-analyses studies have addressed this topic, a comprehensive summary of existing reviews has not been available. Therefore, this umbrella review aims to consolidate the findings on antenatal depression and associated factors among pregnant women in Ethiopia. Methods This review included five systematic reviews and meta-analyses from various databases, including PubMed, PsycINFO, Research4life, CINHALE and Science Direct. Only reviews published between January 1, 2010, and July 30, 2024, were considered. The search, conducted from August 5 to 15, 2024, used CoCoPop questions and included only English-language reviews. Study quality was assessed with the AMSTAR tool, and data extraction and analysis were performed using Microsoft Excel 2016 and STATA 14.0. The I2 and Cochran’s Q tests were used to assess heterogeneity. Pooled effect sizes were calculated based on the pooled prevalence of antenatal depression and odds ratios for associated factors, with a 95% confidence interval indicating statistical significance. Results This umbrella review encompassed 50 primary studies from five systematic reviews and meta-analyses, involving a total of 25,233 pregnant women. The pooled prevalence of antenatal depression in Ethiopia was found to be 24.60% (95% CI: 22.46–26.73). Significant associations were identified between antenatal depression and several factors: unplanned pregnancy (POR = 2.29; 95% CI: 1.75, 2.82), poor social support (POR = 2.10; 95% CI: 1.37, 2.84), history of abortion (POR = 2.49; 95% CI: 1.64, 3.34), history of depression (POR = 3.57; 95% CI: 2.43, 4.71), and history of obstetric complications (POR = 2.94; 95% CI: 1.61, 4.28). Conclusions The significant prevalence of antenatal depression (24.60%) among pregnant women in Ethiopia is closely linked to factors such as unplanned pregnancy, poor social support, history of abortion, previous depression, and obstetric complications. To tackle this issue, it is recommended to enhance social support networks, increase access to family planning services to minimize unplanned pregnancies, conduct regular mental health screenings, and incorporate mental health services into antenatal care.